Investigating the Role of Oxidative Stress and Immune Response in Rheumatoid Arthritis - Sawsan Salman Hosi; Zainab Samir Yahya Hammo; Yaseen Khashman Hussein; Zaid Mohammed Mubarak Almahdawi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background:Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune sickness characterized with the aid of persistent joint infection, leading to joint damage and useful impairment. The pathogenesis of RA is thought to be encouraged with the aid of each genetic and environmental elements, with immune device dysregulation playing a valuable role in ailment progression. Increasing proof shows that oxidative pressure, which results from an imbalance between reactive oxygen species (ROS) and antioxidant defenses, contributes to the inflammatory techniques and tissue harm seen in RA. Objectives: This take a look at aimed to investigate the relationship among oxidative pressure and immune machine dysregulation inside the pathogenesis and progression of rheumatoid arthritis (RA). Methodology:This look at turned into conducted from 1st April to 30 November 2024 and protected a total of 200 participants were covered inside the examiner, along with 150 RA patients (75 male and 75 female) and 50 wholesome controls (25 male and 25 lady). The individuals’ ages ranged from 35 to 75 years. Blood samples were collected from the outpatient clinics at Tikrit Teaching Hospital among April and October 2024, and RA patients have been identified primarily based on medical criteria with the aid of the attending physicians. Oxidative strain markers, along with malondialdehyde (MDA) and glutathione (GSH), and pro-inflammatory cytokines, together with IL-1β, IL-17, and TNF-α, had been measured. Disease interest became assessed the usage of the Disease Activity Score 28 (DAS28). Results:The effects revealed that each male and female RA patients had extensively higher levels of MDA and decrease GSH tiers compared to the healthy manage institution. Moreover, seasoned-inflammatory cytokines (IL-1β, IL-17, and TNF-α) had been appreciably improved in RA sufferers, indicating a country of chronic infection. The DAS28 ratings confirmed that a majority of the RA patients had moderate to excessive disorder hobby. No good sized gender-based variations have been discovered in oxidative strain markers, cytokine stages, or sickness interest rankings. Conclusions: Our take a look at highlights the essential interaction among oxidative strain and immune dysregulation in RA. The determined correlations among oxidative markers, pro-inflammatory cytokines, and disease severity underscore the capability for focused on these pathways inside the management of RA. Future studies are warranted to in addition explore the healing ability of antioxidant-primarily based and anti-cytokine treatments in ameliorating RA-associated inflammation and joint damage. Further research is needed to explore the underlying mechanisms and capacity treatments focused on oxidative stress and immune modulation in RA.